Pentingnya Pembangunan dan Pemberdayaan Gender Dalam Rangka Upaya Mendukung Pembangunan Manusia Provinsi DKI Jakarta - Darwin Hartono (STIE AMKOP, 2023)
The purpose of this research is to examine the effect of gender development and gender empowerment on human development in DKI Jakarta in 2010-2021. This type of research is associative research with a quantitative approach. The analytical method used is multiple regression analysis. The results of the study showed a constant value of 78.292 meaning that if the independent variables IPG and IDG remained or did not change, assuming cateris patribus then human development will increase 78.292 percent. Gender development has a positive and significant impact on human development with coefficient of 4.522. Gender empowerment has a positive and significant impact on human development with a coefficient of 0.451. The results of Adjusted R Square are 0.844 or 84.4 percent, thus the gender development and gender empowerment variables are able to determine the dependent variable of human development by 84.4 percent. The results of the F test show that the F count is 15.864 greater than the F table value with df (0.05;2;12) of 3.884 with a probability value of 0.001. Thus, gender development and gender empowerment have a significant positive effect on the variable human development. The results of the t test show that the gender development variable has a significant positive effect on human development as well as gender empowerment which has a significant positive effect on human development. Keywords: human development, gender development and gender empowerment